Potencial funcional e perfis de compostos fenólicos, carotenóides e fibras de cultivares de laranjas e tangerinas e conservação pós-colheita da tangerina ‘Dancy’ da citricultura familiar - Silva, Antonio Fernando da (2019)
Citrus are part of the diet, being among the most cultivated fruit trees in the world. Brazil is one of the largest citrus‘ producers and exporters, concentrating its production in the Southeast and Northeast of the country. The Borborema Territory-PB produces oranges and tangerines that supply the regional market, which requires in-depth studies to value and insert these fruits in the global market. It is need to define identity and quality standards, functional compound profiles of juice and peels, as well as clean alternatives for postharvest conservation, such as biodegradable coatings. This work evaluated the citrus produced in the Borborema Territory through three main experiments: I - Characterization of bioactive compoundand fiber profile and antioxidant activity of the peel and pulp of orange and tangerine cultivars; II - Postharvest preservation of tangerine with starch coating added with natural deep eutectic solvent (NADES); and III - Quality of orange fruits during ripening. Main results: Experiment I, It was evaluated on the juice and peel of fruits of 10 orange cultivars (Baianinha, Salustiana, Rubi, Westin, Sincorá, Lima, Baia, Common, Mimo, Pera) and 6 tangerines (Piemonte, Clemenules, Page, Dancy, Ponkan and Murcot), the fiber, mineral, free and bonded phenolic, carotenoid profiles in the peels; in addition to the antioxidant activity (TAA) by the radicals ABTS, DPPH and ORAC methods. Citrus peels have high levels of dietary fiber and minerals, are rich in polyphenols, with Dancy standing out in free phenolics (1.46 g GAE. 100g-1 DM) and bonded (0.95 g GAE. 100g-1 DM ) hesperidin (239.99 mg.100g-1), mandarin (46.94 mg.100g-1), chlorogenic acid (118.05 mg.100g-1) and caffeic acid (86.76 mg.100g-1). Tangerine‘s pulp and peels have high levels of carotenoids. TAA of free and bound phenols by ABTS, DPPH and ORAC confirm a higher functional potential of citrus peels. The 'Dancy' tangerine had the highest bouns phenolics TAA. Experiment II: Postharvest conservation of 'Dancy' tangerine was evaluated, with cassava and jackfruit starch, associated with glycerol or a deep eutectic natural solvent (NADES), in DIC, 5 x 6 factorial (coating x evaluation periods ), AM + NADES, AM + GLI, AJ + NADES, AJ + GLI and control, with three replications of 4 fruits each. The coatings maintained the quality of the fruits during storage. Experiment III: A 3x3 factorial DIC was used to evaluate the quality of three orange cultivars ('Baía', 'Comum' and 'Mimo-do-Céu'), three maturation stages (green; yellowish green and yellow), albedo and juice were evaluated. The quality of 'Baia' and 'Mimo-do-Céu' oranges is in line with CEAGESP standards. 'Mimodo-Céu' has a higher ascorbic acid (50.26 mg.100g-1). During maturation, firmness decreased and soluble solids, PET and the TAA of juice and albedo increased. In general, albedo has a poliphenol content about eight-fold higher than that of juice, which reflects in TAA much higher in this portion, which, therefore, stood out for its high functional potential, especially in the ‗Baia‘ orange. Cultivars of oranges and tangerines in this study have high levels of fibers and bioactive compounds essential for human consumption and the tested coatings allow for greater conservation, maintaining quality, which allows transit to much distant competitive markets.